ANIMASI STANDAR OPERASIONAL PROSEDUR STMIK BANDUNG: Studi Kasus : Kampus STMIK Bandung - Mina Ismu Rahayu; Dani Pradana Kartaputra; Anjar Ahmad Nurjaman (LPPM STMIK BANDUNG, 2020)
Geographical information system is a combination of three main elements namely system, information and geography. By paying attention to the understanding of information systems, the geographic information system is a formal unit consisting of various physical and logical resources relating to objects contained on the surface of the earth. Cianjur Regency is one of the regencies in West Java Province. The house has always been a priority for humans as a primary need to meet a comfortable survival for humans themselves. the need for information quickly and precisely, has become a basic need for the community, especially regarding information. Cianjur, as one of the regencies with a geographical situation that is starting to get crowded and the needs of people who want to find information about housing, quickly makes geographic information very helpful for them. The making of this system uses the waterfall model design method, while the diagrams used in the analysis and design are Context Diagrams, Level 1 Data Flow Diagrams and Table Relations. The programming language used in building applications uses the PHP (Hypertext Preprocessor) programming language, MySQL functions as SQL (Structured Query Language) and Sublime Text.